Pengaruh Financial Distress, Growth Rate, Dan Opini Audit Terhadap Auditor Switching Pada Green Business Di Bursa Efek Indonesia Tahun 2019-2023 - Sucipto Febrianto; Puspa Rini; Novriza Wahyu Ardiyansyah (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The present study focuses on the impact of growth rate and audit opinion on financial distress, as well as the rotation of auditors among environmentally conscious companies listed on the Indonesian stock exchange from 2019 to 2023. The present study employs a quantitative, descriptive methodology, utilizing a purposeful sample. The Stichprobe is comprised of eight eco-friendly corporations that are listed on the Indonesian stock exchange within the specified time frame. The analysis of data is performed through the implementation of descriptive statistics and logistical regression techniques, with the software SPSS 30 serving as the primary analytical instrument. The findings of this study indicate that financial distress and growth rate exert a positive, albeit non-significant, influence on the replacement of a financial auditor. In contrast, the audit opinion demonstrates no discernible positive or significant influence on the replacement of a financial auditor. Furthermore, financial distress, growth rate, and audit confirmation are found to have no impact on the replacement of the auditor for green companies listed on the Indonesian stock exchange between 2019 and 2023.